2021
DOI: 10.1101/2021.01.14.426641
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Screening of beans (Phaseolus vulgarisL.) genotypes for drought tolerance

Abstract: Drought is an important factor limiting crop yield and food insecurity globally. Sixty- percent of the bean production areas are prone to drought and subsequently result in eighty-percent of yield reduction. It is emerging as a rising threat to farming communities in Bhutan. Limited studies on crop drought tolerance done in Bhutan. Six bean genotypes (Orey serbu, Orey regtang, Orey brokchilu, Yadhipa orey, Kerongree orey, Brokopali) chose to ascertain drought tolerance. The study was a factorial experiment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Khalil et al [55] proved the role of soil texture on tolerance to water stress related to the decrease in fresh weight in roots and shoots. Similar results have been reported on other growth parameters, such as the reduction in vegetative growth or the number of leaves in Phaseolus vulgaris [56,57]. Emam et al [58] investigated the impact of water stress on the growth and development of two common bean cultivars and concluded that all growth parameters were significantly reduced with moisture deficit.…”
Section: Discussionsupporting
confidence: 68%
“…Khalil et al [55] proved the role of soil texture on tolerance to water stress related to the decrease in fresh weight in roots and shoots. Similar results have been reported on other growth parameters, such as the reduction in vegetative growth or the number of leaves in Phaseolus vulgaris [56,57]. Emam et al [58] investigated the impact of water stress on the growth and development of two common bean cultivars and concluded that all growth parameters were significantly reduced with moisture deficit.…”
Section: Discussionsupporting
confidence: 68%
“…However, more research is required in this area. Previous study in soybean also reported a decline in flower load, and seed-set percentage when exposed to drought stress during the gametogenesis-bloom period 55,56 . Apparently, the injury to flowers or pollen caused by drought directly affected seed number, particularly in cultivars that are sensitive to drought stress.…”
Section: Discussionmentioning
confidence: 73%